Nosocomial Infection Prevention through Universal Precaution in Yogyakarta Muhammadiyah Hospital - Triani Marwati; Siti Kurnia Widi Hastuti; Lina Handayani; Solikhah Solikhah; Lafi Munira (Intelektual Pustaka Media Utama, 2016)
Prevention of nosocomial infections in hospitals can be done through the implementation of universal precaution program or action asepsis and antisepsis tapping. These actions undertaken by health workers, both nurses and physicians, universal precaution measures include: hand washing, use of gloves, use aseptic liquid, processing of used equipment and waste disposal. The purpose of this study to determine the prevention of nosocomial infections in hospitals through universal precautions in hospitals Muhammadiyah Yogyakarta area. Design of this research is descriptive qualitative case study approach. Collecting data used techniques focus group discussions. Data analyzed using content analysis. The application of universal precautions in hospitals throughout Yogyakarta PKU show that health workers have attempted to implement universal precautions including hand washing action on the water flow, perform hand hygiene, and always tries to wear personal protective equipment. Nurses knowledge about nosocomial infections has been well and for prevention need to implement universal precautions. The attitude of nurses in implementing universal precautions have been good, to the extent responsible. Most hospitals have had the availability of facilities and support the implementation of universal precaution well, and partly still exist limitations in the availability of facilities and support the implementation of universal precaution.